2014
DOI: 10.1016/j.bmc.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, [18F] radiolabeling, and evaluation of poly (ADP-ribose) polymerase-1 (PARP-1) inhibitors for in vivo imaging of PARP-1 using positron emission tomography

Abstract: Imaging of poly (ADP-ribose) polymerase-1 (PARP-1) expression in vivo is a potentially powerful tool for developing PARP-1 inhibitors for drug discovery and patient care. We have synthesized several derivatives of benzimidazole carboxamide as PARP-1 inhibitors, which can be 18F-labeled easily for positron emission tomographic (PET) imaging. Of the compounds synthesized, 12 had the highest inhibition potency for PARP-1 (IC50 = 6.3 nM). [18F]12 was synthesized under conventional conditions in high specific activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 31 publications
1
69
0
1
Order By: Relevance
“…AG14361-which has been shown to be specific to PARP1 (32)-and its derived radiotracers feature a benzimidazole instead of rucaparib's fluorinated indole. 18 F-FluorThanatrace ( 18 F-FTT) (23,(33)(34)(35) (IC 50 , 6.3 nM), which replaces dimethyl phenylmethanamine on AG14361 with 18 F-fluoroethoxy benzene, was first tested in MDA-MB-436 and MDA-MB-231 xenografts. PET imaging showed 3-5 %ID/g tumor uptake after 60 min, which was reduced to 2 %ID/g after olaparib blocking.…”
Section: Radiolabeled Probes Structurally Similar To Rucaparibmentioning
confidence: 99%
“…AG14361-which has been shown to be specific to PARP1 (32)-and its derived radiotracers feature a benzimidazole instead of rucaparib's fluorinated indole. 18 F-FluorThanatrace ( 18 F-FTT) (23,(33)(34)(35) (IC 50 , 6.3 nM), which replaces dimethyl phenylmethanamine on AG14361 with 18 F-fluoroethoxy benzene, was first tested in MDA-MB-436 and MDA-MB-231 xenografts. PET imaging showed 3-5 %ID/g tumor uptake after 60 min, which was reduced to 2 %ID/g after olaparib blocking.…”
Section: Radiolabeled Probes Structurally Similar To Rucaparibmentioning
confidence: 99%
“…Radiosynthesis was done in accordance with current Good Manufacturing Practices (cGMP) for PET radiopharmaceuticals. 23 …”
Section: Introductionmentioning
confidence: 99%
“…21 We have previously shown that these radiotracers bind to PARP in vivo by using breast cancer tumor models and can be competitively blocked by using a clinical PARP inhibitor. 22,23 In this study, we explored a PARP-1 PET imaging agent [ The cell lines used in this study were selected based on the genetic profile as either ovarian cancer BRCA1 mutant (SNU-251) or BRCA1 functional-wild type (SKOV3). We hypothesize that [ 18 F]FTT uptake in vitro will correspond to PARP-1 expression, and ovarian cancer cells with higher PARP-1 expression will be more sensitive to PARP inhibition adjuvant to radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The low specific activity of 18 F-PARPi-Fl, which is radiolabeled with 18 F for 19 F exchange, likely will limit the clinical utility of this probe. 18 F-fluorthanatrace showed high uptake in a breast tumor with a high level of expression of PARP1; this uptake could be blocked with olaparib, suggesting that this uptake was specific to PARP1 expression (52). A phase 0 clinical trial of 18 F-fluorthanatrace is currently being conducted at Washington University, and new trials on other tumor types and in various therapeutic settings are planned.…”
Section: How Can Patients Who Will Respond To Parp Inhibitors Be Idenmentioning
confidence: 99%